Production of inulinase from Kluyveromyces marxianus using Dahlia tuber extract - Jain,Sumat Chand (2012)
Various carbon sources were evaluated for production of inulinase by yeast, Kluyveromyces marxianus MTCC 3995. Highest inulinase activity was observed with Dahlia extract (25.3 nkat mL-1) as carbon source. The enzyme activity was 1.4 folds higher than that observed in media containing pure chicory inulin (17.8 nkat mL-1). The yeast showed good growth on a simple medium containing dahlia extract (20% w/v) and yeast extract (2%w/v) as carbon and nitrogen source respectively, in 96 h. at 28°C and 120 rpm. Lowest inulinase yield (4.8 nkat mL-1) was seen in the medium containing glucose as C-source. Although varied inulinase levels were noticed on different C- sources, Inulinase: Sucrase (I/S) ratios were noticed to be similar. Among various protein sources tested, yeast extract was found to be the best source followed by beef extract (17.9 nkat mL-1) and peptone (13.8 nkat mL-1). The enzyme was optimally active at pH (4.0) and 50°C. TLC analysis of end product revealed that inulinase hydrolyzed inulin exclusively into fructose. Results suggest that the dahlia extract induced exoinulinase synthesis in Kluyveromyces marxianus and can be utilized as a potential substrate for inulinase production.